Rate of Germination, Seedling Vigour and Field Emergence in Pearl Millet Hybrids and their Parents - Raj, lekh; Khairwal, I S (Annals of Arid Zone, 2016)
Hybrids and the cytoplasmic male sterile lines had the same germination percentage, but the hybrids showed higher germination index and the rate as well. Hybrids also had higher dry weight per seedling, vigour index and seedling vigour in the field. Significant and positive correlations were found between standard germination and field emergence, and also between dry weight per seedling, vigour index and seedling vigour.